2018
DOI: 10.1002/hbm.24311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of cognitive impairment in patients with Parkinson's disease and its related pattern in 18F‐FDG PET imaging

Abstract: This study aimed to characterize the clinical features and the related cerebral glucose metabolism pattern of cognitive impairments in Parkinson's disease (PD) with positron emission tomography (PET) imaging. We recruited 168 PD patients and 100 age-matched healthy controls of similar education and gender distribution. All of those enrolled underwent clinical assessment including the unified Parkinson's disease rating scale motor score, Hoehn and Yahr scale, and comprehensive neuropsychological tests including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 48 publications
(81 reference statements)
2
26
0
1
Order By: Relevance
“…Putamen-related motor circuits were responsible for motor functions, and disruption of putamen function correlated well with the onset of cardinal motor symptoms 34 and motor severities, 10,35 whereas caudate was more likely to be involved in the circuits related to cognitive and affective functions. 3638 Patients with caudate lesion suffered from cognitive changes, including poor planning and sequencing. 39 In the current study, DAT binding in caudate correlated moderately with TMT-A test scores.…”
Section: Yopd Exhibited a Different Dopaminergic Disruptive Pattern Imentioning
confidence: 99%
“…Putamen-related motor circuits were responsible for motor functions, and disruption of putamen function correlated well with the onset of cardinal motor symptoms 34 and motor severities, 10,35 whereas caudate was more likely to be involved in the circuits related to cognitive and affective functions. 3638 Patients with caudate lesion suffered from cognitive changes, including poor planning and sequencing. 39 In the current study, DAT binding in caudate correlated moderately with TMT-A test scores.…”
Section: Yopd Exhibited a Different Dopaminergic Disruptive Pattern Imentioning
confidence: 99%
“…Deficits of executive functions correlated with frontal hypometabolism in some studies (92, 93), but not in the others (9496). Furthermore, disruption of the striatal dopaminergic system, shown with [ 18 F]-6-fluorodopa PET imaging, correlated with executive dysfunction in patients with preserved metabolism in the frontal cortex (97), with uncertain explanation.…”
Section: Parkinson's Diseasementioning
confidence: 71%
“…Hypometabolism in parietal and temporal cortices more consistently correlated with executive dysfunction (9296). Attention deficits, regarded by some as an executive dysfunction (99), correlate with hypometabolism in the frontal cortex (95), precuneus and parietal cortex (94) and with the hypermetabolism in the putamen, parahippocampal gyrus, inferior frontal lobule, paracentral lobule, and hippocampus (94). Posterior cholinergic neurodegeneration, marked by the initial decline in visuospatial functioning and followed by memory impairment, can be detected by glucose metabolism changes, too.…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…One study pointed out that regions related to visual processing such as parietal and frontal lobes are altered in patients with cognitive decline associated with PD (Mak et al 2015). Wu et al (Wu et al 2018) found a correlation between the reduction of glucose metabolism in the parietal, temporal, frontal, and cingulate cortex and the pathological pattern of PD using positron emission tomography (PET). These data reinforce our findings, raising the possibility of a new PD biomarker related to visual processing.…”
Section: Discussionmentioning
confidence: 99%